Swarming motility in Bradyrhizobium japonicum - Covelli, Julieta Mariana (2013)
Flagellar-driven bacterial motility is an important trait for colonization of natural environments. Bradyrhizobium japonicum is a soil speciesthat possesses two different flagellar systems: one subpolar and the other lateral, each with a filament formed by a different set of flagellins.While synthesis of subpolar flagellins is constitutive, translation of lateral flagellins was detected in rhizobia grown with L-arabinose, but notwith D-mannitol as sole carbon source, independently of whether bacteria were in liquid or semisolid medium. We characterized swarming of B.japonicum in semisolid medium and found that this motility was faster with L-arabinose than with D-mannitol. By using mutants with deletions ineach flagellin set, we evaluated the contribution of each flagellum system to swarming in semisolid culture media, and in soil. Mutants devoid ofeither of the flagella were affected in swarming in culture media, with this impairment being stronger for mutants without lateral flagella. Insterile soil at 100% or 80% field capacity, flagellar-driven motility of mutants able to swim but impaired in swarming was similar to wild type,indicating that swimming was the predominant movement here.